2019
DOI: 10.7150/thno.34090
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of PCOLCE by TWIST1 promotes metastasis in Osteosarcoma

Abstract: Procollagen C-proteinase enhancer protein (PCOLCE) was originally identified as an enhancer to facilitate the catalysis of procollagens by BMP1. PCOLCE participates in the reconstitution of extracellular and corneal repair. The elevation of PCOLCE in blood indicates that breast cancer has metastasized into the bones. However, direct research on PCOLCE has not been reported. Methods : ECM candidates were identified by RNA-seq analysis from 4 normal and 16 osteosarcoma tissues. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 34 publications
(37 reference statements)
2
50
0
Order By: Relevance
“…In recent decades, the highthroughput sequencing technologies have greatly facilitated the understanding of metastasis-related genes function by decoding the genome of cancer patients [26]. An increasing number of researchers have also concentrated on exploring the underlying pathogenesis of OS metastasis [27,28]. Moreover, building a prediction model of OS metastasis was growingly important for prognostication and clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, the highthroughput sequencing technologies have greatly facilitated the understanding of metastasis-related genes function by decoding the genome of cancer patients [26]. An increasing number of researchers have also concentrated on exploring the underlying pathogenesis of OS metastasis [27,28]. Moreover, building a prediction model of OS metastasis was growingly important for prognostication and clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…For the subcutaneous tumor model, 1 × 10 6 shNC, shWTAP or shHMBOX1 or shWTAP/ shHMBOX1 U2OS cells seeded into mice via subcutaneous injection. Tumor volume and tumor weight were measured to analyze tumor growth as previous described 46 . For orthotopic xenograft tumor model, shNC, shWTAP, shHMBOX1, or shWTAP/shHMBOX1 U2OS cells were labeled with a luminescent dye and GFP, and injected into the cavity of the tibia of mice.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…CBX4 functions by transcriptionally upregulating Runx2. To identify the key molecules in the progression of osteosarcoma, RNA-seq was recently performed using 16 osteosarcoma tissues and 4 normal tissues ( Supplementary Table 1) 15 . We found that CBX4 and CBX8, but not CBX2 or CBX6, was overexpressed in all 16 osteosarcoma tissues compared with the 4 normal tissues ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%